MYCOBACTERIUM SIMIAE INFECTION IN AN IMMUNOCOMPETENT ELDERLY WOMAN: CASE REPORT IN RORAIMA STATE OF BRASIL - Sequeira, Bianca Jorge; Muniz, Dalet Zaine Freitas; Cedro, Carla Vitória Damasceno Rodrigues; Turpo, Karen Patrícia Gutierrez; Monção, Tâmara Vieira; dos Santos, Nayara Melo; Araújo, Jucineide Vieira; Carbonell, Roberto Carlos Cruz (Saúde (Santa Maria), 2021)
A Mycobacterium simiae pulmonary infection in an eighty-year-old patient attended to at the Tuberculosis Secondary Referral Outpatient Clinic in the city of Boa Vista, Roraima between 2016 and 2019. This study aims to report the symptoms, diagnostic methods, and treatment of the patient because for this rare case in Brazil, and this patient had a late and difficult diagnosis. Due to this difficulty, the patient was treated for pulmonary tuberculosis for years without being cured. Finally, after a correct diagnosis, the treatment was stopped due to failure.